Предмет:
АлгебраАвтор:
kokolarsenАвтор:
buttercupi42rАвтор:
harleyszr6Автор:
tequilaqpjwАвтор:
darrylhullАвтор:
anselmotssfРазложим выражение на множители:
(7+n)² - n² = (7+n-n)(7+n+n) = 7(7+2n)
Один из множителей 7, следовательно, выражение кратно семи.
Автор:
halledrake(7+n)²-n²=7·7+2·7·n+n²-n²=7·7+2·7·n=7·(7+2·n) делится на 7
вот так:
7·(7+2·n) : 7 = 7+2·n
Автор:
timothy7xk9Добавить свой ответ
Предмет:
МатематикаАвтор:
cherishgainesОтветов:
Смотреть
Предмет:
ХимияАвтор:
enriquesantosОтветов:
Смотреть
Предмет:
МатематикаАвтор:
gamsОтветов:
Смотреть
Предмет:
Английский языкАвтор:
rosieaaxsОтветов:
Смотреть